Disaggregating Mass Public Shootings: A Comparative Analysis of Disgruntled Employee, School, Ideologically motivated, and Rampage Shooters. Issue 3 (18th December 2018) - Capellan, Joel A.; Johnson, Joseph; Porter, Jeremy R.; Martin, Christine
Abstract: This study compares the demographic, background, motivation, and pre‐event and event‐level behaviors across four types of mass public shooters: disgruntled employee, school, ideologically motivated, and rampage offenders. Using a database containing detailed information on 318 mass public shootings that occurred in the United States between 1966 and 2017, we find systematic differences in the characteristics, motivations, target selection, planning, and incident‐level behaviors among these offenders. The results show that ideologically motivated shooters to be the most patient, and methodical, and as a result the most lethal. Conversely, disgruntled employees, who are driven by revenge, tend to have little time to plan and consequently are the least lethal shooters. These, among other differences, underscore the need for prevention strategies and policies to be tailored to specific types of offenders. Furthermore, the results also highlight commonalities across offender type, suggesting that the social and psychological pathways to violence are universal across offenders.